(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2024)
Objectives: The aim of this study was to compare the outcome of hypospadias repair by tubularisation of an intact and laterally augmented urethral plate urethroplasty and TIP urethroplasty. Methods: This prospective comparative study was conducted from July 2018 to January 2020 and included 35 patients with primary distal and mid penile hypospadias. All had urethral plate widths of 8–10 mm. Exclusion criteria were mega meatus intact prepuce, previous repair, circumcision, urethral plate of >10 mm or <8 mm in diameter, chordee >30°. In Group A underwent tubularisation of an intact and laterally augmented urethral plate urethroplasty and in Group B underwent tubularised incised-plate (TIP) urethroplasty. The follow up period was 06 months. Results: The success rate without any complication was 88.89% and 76.48% in Group A and B respectively. Meatal stenosis occurred 0% and 11.76% in Group A and B respectively. Wound dehiscence rate was 5.55% and 5.88% in Group A and B respectively. Urethrocutaneous fistula occurred 5.55% and 5.88% in Group A versus Group B. Overall complication occurred 11.11 in Group A and 23.52% in Group B. Conclusion: The outcome of tubularisation of intact and laterally augmented urethral plate urethroplasty was better than TIP urethroplasty. Journal of Paediatric Surgeons of Bangladesh (2019) Vol. 10 (1 & 2): 32-36